Extremist deradicalisation programmes: a comparative perspective - Bakashmar, Muhammad R. (Trans Stellar Journal Publications, 2015)
This paper presents a comparative perspective of a sample of deradicalisation programmes in various parts of the world. Deradicalisation is conceptualized as the unraveling of 1Cradicalization 1D i.e. a process in which individuals proceed from the state of passivity to radicalism through the adoption of extremist ideology while gradually increasing the likelihood of their involvement in violent radical behavior. The programmes reviewed cover a wide range of political,cultural and religious backgrounds from the Scandinavian countries to continental Europe, the Middle East, Southeast Asia as well as Australia. Special attention is given to deradicalisation processes in prisons around the world. KEYWORDS: Deradicalisation Programmes, Radicalisation